Localization and distribution of CCK-8‑, NPY‑, Leu-ENK-, and Ghrelin- in the digestive tract of prochilodus lineatus (Valenciennes, 1836) - Barrios, Carlos Eduardo (2020)
This study describes the histological characteristics and distribution of gastrointestinal tract endocrine cells (ECs) of Prochilodus lineatus (detritivorous fish) using immunohistochemical procedures. The digestive tract of P. lineatus was divided into seven portions: stomach (cardial and pyloric), pyloric caeca, and intestine (anterior, glandular, middle and posterior). A pool of specific antisera against cholecystokinin (CCK-8), -neuropeptide Y (NPY), -ghrelin (Ghre) and -leu-enkephalin (Leu-ENK) to identify ECs were used. According to the morphological characteristics of ECs, two different types were identified and classified as open or closed-type. The number of ECs varied throughout the gastrointestinal tract, though a high abundance was found in the anterior intestine and pyloric caeca. A large number of ECs immunoreactive to CCK-8 and NPY were recorded in the anterior, glandular and middle intestine. ECs immunopositive to Leu-ENK were distributed in the stomach and pyloric caeca. For Ghre, immunopositive ECs were restricted to the glandular intestine. The results of the present study indicate that P. lineatus presents an ECs distribution pattern with species-specific particularities. However, CCK showed a distribution similar to that of omnivores, which is possibly related to local signaling functions in order to achieve the correct digestion of the various organisms found in the detritus.